FACTORS AFFECTING CRITICAL THINKING STUDENT - Phromkat, Phongnapha (Journal of MCU Nakhondhat, 2023)
This article is an academic article aimed at presenting factors affecting the critical thinking of teachers toward students. Authors synthesize and summarize academic articles from books, documents, textbooks, journals, theses, research papers, and the Internet. can be summarized as follows ; 1) The ability and good relationship of instructors with students was the person who had a good interpersonal relationship between instructors and students from caring and attentive. 2) Reading habit factor. The most important thing to encourage students to develop critical thinking skills. Students must know and use the correct way of reading to practice themselves regularly. Teachers must emphasize the use of teaching methods for students to learn by themselves. This will be a factor conducive to reading to create critical thinking. 3) Factors on learning attitude. Instructors must have preparation for teaching, including media, materials, equipment, documents and activity manuals. and the process of organizing activities was prepared to encourage students to develop critical thinking skills. Highly motivated students are capable of planning, thinking critically in order to achieve the standards of excellence they set. 5) Classroom climate factor. Teachers must provide a classroom atmosphere that is a factor in encouraging students to be motivated, challenged, trusted, fun, and willing to take risks. The classroom atmosphere contributes to and facilitates students to think critically effectively